A Rossby whistle: A resonant basin mode observed in the Caribbean Sea. Issue 13 (2nd July 2016) - Hughes, Chris W.; Williams, Joanne; Hibbert, Angela; Boening, Carmen; Oram, James
Abstract: We show that an important source of coastal sea level variability around the Caribbean Sea is a resonant basin mode. The mode consists of a baroclinic Rossby wave which propagates westward across the basin and is rapidly returned to the east along the southern boundary as coastal shelf waves. Almost two wavelengths of the Rossby wave fit across the basin, and it has a period of 120 days. The porous boundary of the Caribbean Sea results in this mode exciting a mass exchange with the wider ocean, leading to a dominant mode of bottom pressure variability which is almost uniform over the Grenada, Venezuela, and Colombia basins and has a sharp spectral peak at 120 day period. As the Rossby waves have been shown to be excited by instability of the Caribbean Current, this resonant mode is dynamically equivalent to the operation of a whistle. Key Points: There is a 120 day Rossby wave resonant mode in the Caribbean Sea The mode strongly affects coastal sea level and dominates bottom pressure The mode operates in a manner dynamically equivalent to a whistle